THE TOTAL VERTEX-IRREGULAR STRENGTHS OF PATH DOUBLE DIGRAPHS, CYCLE DOUBLE DIGRAPHS, FAN DOUBLE DIGRAPHS, AND FRIENDSHIP DOUBLE DIGRAPHS - HERAWATI , SUSI
In this thesis we study the vertex-irregular total k-labeling and the total vertex-irregular strengths of some double digraphs, namely: paths, cycles, fans, and friendships.